Dispositif d'accompagnement hybride dans un cours de physique de première année à l'université en Belgique - Elisabeth Gruwé (Nantes Université, 2023)
Our study focuses on implementing and analyzing the first version of a "flipped classroom" hybrid tutoring program, as part of an action research in a first-year university physics course. Guided by the contributions of several fields of literature, we designed the program to improve interactions between peers and with the teacher, and mitigate students' tendency towards passivity during group exercise sessions. Our analysis first focused on the students' perceptions of the program, collected in an open and closed-ended questionnaire. To identify at-risk student profiles in the course, we also constructed statistical models to explore the links between the socio-demographic characteristics and past schooling of first-time enrolled students, their participation in the program, and the grade obtained on the exam. Based on the results, we discuss avenues to be explored in future analyses and adaptations to be made to the second version of the program.